(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article is devoted to the analysis of the role of existentialist writers in the contemporary Russian literary process of the 21st century. It examines key aspects of their influence, including the exploration of post-Soviet identity, dialogue with global philosophy, the integration of existential motifs with postmodernist techniques, and the critique of social realities. Special attention is given to the works of authors such as Viktor Pelevin, Evgeny Vodolazkin, and Vladimir Sorokin, whose writings illustrate the combination of philosophical depth with experiments in form and content. The article highlights how existentialist ideas enrich the literary process, fostering reflection on the meaning of existence and expanding the boundaries of contemporary Russian literature.